Social Housing for Young Adults in Kielce, Poland - Teriyapirom, Arisa (Vysoké učení technické v Brně. Fakulta architektury, 2023)
Social Housing for Young Adults in Kielce, Poland is a diploma project that focuses on the revitalization of an abandoned university building, art gallery and synagogue into an affordable social housing complex that integrates various forms of social spaces and social activities. The crisis in the housing market and the economic situation has left many young adults struggling to afford rent, or being able to only afford places that are in poor condition and thus they return to their hometown ore move to smaller cities, in order to avoid the extremely high rental prices. Good housing is a necessity, especially for young adults, as they are in a period of transition to adulthood, and requires a proper place to call home. In addition, the project also focuses on a young adult’s life as a whole, this means revitalization of spaces to support a co-working environment, as this is becoming increasingly popular and beneficial to young adults who are working remotely or in non-traditional careers. It also means designing a social space outside the housing block, to give a sense of separation between personal and social life. In this project, the university building is redesigned into social housing, co-living environment, art gallery for canteen, and synagogue for co-working space. The three buildings all come together to create an inclusive, conducive, comfortable, playful environment for young adults in Kielce.

Social Housing for Young Adults in Kielce, Poland is a diploma project that focuses on the revitalization of an abandoned university building, art gallery and synagogue into an affordable social housing complex that integrates various forms of social spaces and social activities. The crisis in the housing market and the economic situation has left many young adults struggling to afford rent, or being able to only afford places that are in poor condition and thus they return to their hometown ore move to smaller cities, in order to avoid the extremely high rental prices. Good housing is a necessity, especially for young adults, as they are in a period of transition to adulthood, and requires a proper place to call home. In addition, the project also focuses on a young adult’s life as a whole, this means revitalization of spaces to support a co-working environment, as this is becoming increasingly popular and beneficial to young adults who are working remotely or in non-traditional careers. It also means designing a social space outside the housing block, to give a sense of separation between personal and social life. In this project, the university building is redesigned into social housing, co-living environment, art gallery for canteen, and synagogue for co-working space. The three buildings all come together to create an inclusive, conducive, comfortable, playful environment for young adults in Kielce.
Social Housing for Young Adults in Kielce, Poland
Keywords: Social housing; revitalization; co-living; co-working; Social housing; revitalization; co-living; co-working